1990
DOI: 10.1177/089124249000400303
|View full text |Cite
|
Sign up to set email alerts
|

The Case for State-Level Export Promotion Assistance: A Comparison of Foreign and Domestic Export Employment Multipliers

Abstract: Most states are currently engaged in some form of foreign export assistance as part of the state's overall economic development strategy. However, this raises the question as to whether scarce state economic development resources should be diverted from the more traditional economic development programs in order to fund foreign export stimulation. This study develops and tests a model to compare the employment multiplier of foreign exports with that of domestic exports. The results indicate that the foreign ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Studies of state international exports, which are more pertinent to the present study, have considered the impacts of foreign exports on state or regional economic growth (Manrique 1987;Zech 1986;Erickson 1989). These studies, which typically do not involve time-series causality tests, have generally found positive, contemporaneous associations between foreign exports and state economic indicators (Zech 1986;Manrique 1987;Coughlin and Cartwright 1987;Erickson 1989;Webster et al 1990). A recent study by Richardson and Smith (1 995), however, comes to the opposite conclusion.…”
Section: Exports and Economic Growth: Theoretical Perspectives And Emmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of state international exports, which are more pertinent to the present study, have considered the impacts of foreign exports on state or regional economic growth (Manrique 1987;Zech 1986;Erickson 1989). These studies, which typically do not involve time-series causality tests, have generally found positive, contemporaneous associations between foreign exports and state economic indicators (Zech 1986;Manrique 1987;Coughlin and Cartwright 1987;Erickson 1989;Webster et al 1990). A recent study by Richardson and Smith (1 995), however, comes to the opposite conclusion.…”
Section: Exports and Economic Growth: Theoretical Perspectives And Emmentioning
confidence: 99%
“…The most pervasive interpretation, that foreign exports are an engine of economic growth, is rooted in traditional export base theory (North 1975). The theory, which was originally developed to account for the role of natural resourceintensive exports such as lumber in the historical development of regional economies, suggests that direct and indirect multiplier effects associated with export expansion represent a driving force generating regional economic growth (Innis 1995;North 1966North , 1975Webster et al 1990). An autonomous rise in export demand leads to growth in regional income which, in turn, increases local demand causing additional income growth, and so forth.…”
Section: Exports and Economic Growth: Theoretical Perspectives And Emmentioning
confidence: 99%
“…Regional development applications typically focus on the interregional exports of a local area within a national economy. The idea that exports provide an engine of growth is also frequently applied in studies of the regional and national impacts of foreign export growth (e.g., Feder 1982;Kavoussi 1984;Webster, Mathis, and Zech 1990). Although numerous methodological approaches have been developed to define the export base, the most recent of which involve the application of advanced timeseries methods (Brown, Coulson, and Engle 1992) and the use of dummy variables to distinguish between different types of communities (Mulligan and Fik 1994), the debate over this issue continues.…”
Section: Export Base Theorymentioning
confidence: 99%
“…Although numerous methodological approaches have been developed to define the export base, the most recent of which involve the application of advanced timeseries methods (Brown, Coulson, and Engle 1992) and the use of dummy variables to distinguish between different types of communities (Mulligan and Fik 1994), the debate over this issue continues. The idea that exports provide an engine of growth is also frequently applied in studies of the regional and national impacts of foreign export growth (e.g., Feder 1982;Kavoussi 1984;Webster, Mathis, and Zech 1990). These studies emphasize both the income multiplier effects and the externality benefits thought to occur with the growth of exports, but they do not directly address the issue of causality between exports and economic growth.…”
Section: Export Base Theorymentioning
confidence: 99%
“…State governments spent nearly $100 million in FY 1990 on international programs, a majority of which were devoted to export promotion activities (NASDA 1991). Empirical support for such programs has been forthcoming in recent research that supports a positive influence of industrial exports on state manufacturing growth (Coughlin and Cartwright 1987a;Erickson 1989;Markusen, Noponen, and Driessen 1991) and relatively higher multipliers for foreign exports than interstate domestic exports (Webster, Mathis, and Zech 1990). However, the precise nature of the complex causality involved in the relationship between exporting and state economic growth has been called into question (Erickson 1989;Markusen et al 1991), with some suggestion that greater success in export markets arises from a base of strong domestic sales growth.…”
Section: Introductionmentioning
confidence: 99%